How does the household structure shape the urban economy? - Stefan Tscharaktschiew; Georg Hirte (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
Households in real cities are heterogeneous regarding their size and composition. This implies that the household structure -i.e. the (average) household size, the composition, the relative share of different household types, and the number of households - differs across cities. This aspect is usually neglected in urban models used to study economic and policy issues that arise in today's cities. Furthermore, the household structure might change over time. For instance, over the last decades average household size has decreased in many countries. Several implications of this change have been discussed, but usually not in regard to an urban economy with its interdependencies. We develop an applied urban general equilibrium model which explicitly takes the household structure into account and thus allows studying the impacts of changes in the household structure on an urban economy and its spatial pattern. The paper shows that changes in the household structure affect an urban economy in various ways and may contribute to explain economic and spatial effects on cities. Compared to a 'Base City' which reflects the actual household structure in the United States, urban labor force participation, housing demand, rents, wages as well as urban commuting and shopping patterns are considerably affected by, e.g., changes in the average household size in a city. For instance, wage inequality between differently skilled workers rises and extreme cross commuting drops to almost zero when the city turns into a pure 'Singles City'.
Keywords: C68; R12; R13; R14; R20; 330; General equilibrium; Household structure; Household size; Location; Commuting